Geologic feasibility of underground hydrogen storage in Canada. (13th November 2020) - Lemieux, Alexander; Shkarupin, Alexi; Sharp, Karen
Abstract: Electricity production in the majority of Canada's regions is characterized by high proportions of nuclear and renewable sources such as hydroelectricity. Future plans to phase out coal-fired power plants by 2030 and decrease fossil fuel use in favor of increased integration of renewables highlight the need to develop strategies which can match intermittent and base-load electricity output with market demand. The use of hydrogen gas generated through off-peak electrolysis has been highlighted by the Canadian government as a potential avenue forward in managing electrical grids with surplus and intermittent electricity generation. This technology can be supported in a safe and cost-effective manner by underground hydrogen storage in geological formations. In this article, an overview of Canadian geology, as well as an assessment of the potential application of underground storage methods and associated safety concerns in Canada is presented. Favorable locations for pilot projects are found in the sedimentary basins of western and Atlantic Canada as well as southern Ontario, or the crystalline rocks of the Canadian Shield. Highlights: Canada is a world leader in terms of renewable energy production. Growth in the renewable and hydrogen electricity sectors is expected. Excess electricity can be stored as hydrogen gas in the geological subsurface. Many areas of Canada are favorable for underground hydrogen storage.